Astilbin improves the therapeutic effects of mesenchymal stem cells in AKI-CKD mice by regulating macrophage polarization through PTGS2-mediated pathway - Xiaodong Geng; Zhangning Fu; Guangrui Geng; Kun Chi; Chao Liu; Haijuan Hong; Guangyan Cai; Xiangmei Chen; Quan Hong (Stem Cell Research & Therapy)
Abstract Background Although mesenchymal stem cells (MSCs) have been proven to be appropriate candidates for the treatment of AKI-CKD, their efficacy is limited and variable. Astilbin (AST) had a protective effect on MSCs from oxidative stress via ROS-scavenging, however, whether it can improve MSCs’ renoprotection and the underlying mechanism need to be elucidated. Methods AST-pretreated MSCs were administered intravenously into the ischemia–reperfusion injury mice models and the renal function, pathological changes and inflammation. Were evaluated. In addition, DARTS, molecular docking, surface plasma resonance(SPR), dual-luciferase reporter gene assay and the ChIP-PCR were utilized to explore the potential signaling pathways through which AST exert renal protective effects on MSCs. Results AST-pretreated MSCs markedly improved kidney function, reduced kidney pathological injury and inflammation in AKI and AKI-CKD mice. RNA-seq results showed that PTGS2 related pathway was significantly up-regulated in MSCs after AST pretreatment. DARTS assay, molecular docking and SPR assay revealed that AST could bind with the transcriptional factor of Kruppel-Like Factor 4(KLF4) protein. The promoter of PTGS2 had the binding and transcriptional activation by KLF4. Furthermore, AST pretreatment promoted the secretion of PGE2 in MSCs. And then the westren blot results showed that the protein levels of CD163 and CD206 were upregulated after coculture in AST-pretreated MSCs, indicating that the polarization of RAW264.7 cells towards M2-like macrophages was induced. Knockdown of PTGS2 reversed the ability of AST-pretreated MSCs in converting macrophages to M2 phenotype and reducing their therapeutic effects on AKI-CKD mice. Conclusion AST pretreatment enhances the efficacy of MSCs on AKI and AKI-CKD mice by inducing of M2-like phenotype polarization in macrophages through the PTGS2-mediated pathway. This approach not only provides a novel strategy to strengthen the capability of MSCs but also helps elucidate the beneficial effects of the Chinese herbal medicine AST.